Analisis Perbandingan Uji Mekanik Komposit Fiber Glass Serat Anyam dan Serat Acak dengan Metode Vacuum Assisted Resin Influsion dan Hand Lay Up Sebagai Pengganti Radome Pesawat Hercules C-130 - Vebriyola, Fitry; Subijanto, Raden Agus (Akademi Angkatan Udara, 2022)
The purpose of this study was to test the strength and flexibility of thecomposites a woven fiber composite specimen was tested and randomized by the han lay up method and vacuum assisted infusion resin. Using the universal testing machine (quasar 50 qualities) tensile test equitment. From the data processing carried out it can be concluded that the vacuum assisted resin infusion method of woven fiber is stronger in the tensile test. Because in the experimental result the tensile stress and strain strength are geaterin value but the elastic modulus is greater in the vacuum woven fiber method. This is due to the arrangement of fibers which is stronger to withstand the tension in the composite with the vacuum method. So that morefibers are parallel to the tensile direction of the specimen. This causes the maximum tensile stress in the vacuum assisted resin infusion woven fiber composite method compared to the Hercules C-130 Radome Aircraft.